Possibilities and limitations of terrestrial laser scanning for crack detection in building walls - Stałowska, Paulina (International Conference “Environmental Engineering”, 2023)
The inspection of the technical condition of buildings is a highly significant part of the construction field. In particular, symptoms such as cracks are indicators of poor technical conditions of buildings. Currently, technologies that enable remote and non-destructive detection of defects are in great demand. One of these technologies is the Terrestrial laser scanning (TLS) – method very popular in recent years and widely applied in civil engineering. Therefore, surveys have been carried out that have identified the possibilities and limitations of TLS technology for detecting cracks in the walls of buildings. All analyses and discussions were carried out using geometric and radiometric point cloud information.